2018
DOI: 10.3892/mmr.2018.9515
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Nur77 and its ligands as potential anticancer compounds (Review)

Abstract: Nuclear receptor subfamily 4 group A member 1 (NR4A1; also termed Nur77/TR3/NGFIB), a member of the nuclear receptor superfamily, is expressed as an early response gene to regulate the expression of multiple target genes. Nur77 has the typical structure of a nuclear receptor, including an N-terminal domain, a DNA binding domain, and a ligand-binding domain. The expression and localization of Nur77 are closely associated with its roles in cell proliferation and apoptosis. Nur77 was first identified as an orphan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 96 publications
(129 reference statements)
1
44
0
Order By: Relevance
“…NR4A1 (also called Nur77, TR3, or NGFIB) is an orphan nuclear receptor that belongs to the steroid/thyroid/retinoid receptor superfamily (Hazel et al, 1988). NR4A1 contains DNA binding domain (DBD) and ligand binding domain (LBD) (Lin et al, 2004), by which NR4A1 is activated and regulates gene expression (Wu and Chen, 2018). In addition, it plays a significant role in pro-apoptotic function through mitochondrial localization and binding to Bcl-2 (Godoi et al, 2016;Lin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…NR4A1 (also called Nur77, TR3, or NGFIB) is an orphan nuclear receptor that belongs to the steroid/thyroid/retinoid receptor superfamily (Hazel et al, 1988). NR4A1 contains DNA binding domain (DBD) and ligand binding domain (LBD) (Lin et al, 2004), by which NR4A1 is activated and regulates gene expression (Wu and Chen, 2018). In addition, it plays a significant role in pro-apoptotic function through mitochondrial localization and binding to Bcl-2 (Godoi et al, 2016;Lin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…And we found a new target protein Nur77, who play an important role in G-apo A-induced antiangiogenesis. Nur77(NR4A1) is one of the NR4A subfamily, which consists of 3 well conserved members, Nur77, Nurr1 (NR4A2) and NOR-1 (NR4A3), respective [35]. NR4A receptors are immediate-early genes that are regulated by many physiological stimuli including growth factors, hormones, and in ammatory signals and are involved in a wide array of important biological process, including cell apoptosis, brain development, glucose metabolism, and vascular remodeling [36].…”
Section: Discussionmentioning
confidence: 99%
“…In normal conditions Nur77 is found in the nucleus but regulated by phosphorylation, which occurs by MAPK and AKT. Phosphorylation of Nur77 drives the abnormal translocation of the transcription factor to the mitochondria where it causes MOMP ensuing cytochrome c release [110]. The activity of this transcription factor in the context of viral protein cancer toxicity has been mostly studied in CAV-Apoptin.…”
Section: Mitochondrial Cell Deathmentioning
confidence: 99%
“…Interestingly, Nur77 is known to interact with Bcl-2 and turn it from anti-to pro-apoptotic which may explain the conflicting results for this protein [111]. Nur77 is also important for HGV-Apoptin as treatment triggers cytoplasmic translocation of Nur77 93 Nevertheless, although less is known about this transcription factor in other viral protein mechanisms, studies have found that Nur77 interacts with an E1A binding partner p300, and the overexpression of E1A can repress Nur77 transactivation [110,112].…”
Section: Mitochondrial Cell Deathmentioning
confidence: 99%